Promoting Gender Equality Through Paternity Leave in Labour Law Transforming the Role of Fathers in Childcare - Maharani, Desty (Jurnal Pengembangan Ketenagakerjaan, 2024)
Paternity leave plays a critical role in promoting gender equality by encouraging fathers' active involvement in childcare. In Indonesia, the current legal framework, as outlined in Law Number 13 of 2003 Concerning Manpower, provides only two days of paternity leave, which is insufficient for meaningful paternal engagement during the early stages of child-rearing. This article examines the implementation of paternity leave in Indonesia, comparing it to more progressive models from countries such as Sweden, Norway, and Japan, where extended, non-transferable paternity leave policies have been shown to enhance gender equality and improve both child and maternal well-being. Through a review of international case studies, the article argues that the current Indonesian policy needs reform to align with global standards and to better support fathers in their caregiving roles. Recommendations include extending paternity leave, offering financial incentives for employers, introducing flexible parental leave systems, and launching public awareness campaigns to challenge cultural norms. By adopting these changes, Indonesia could foster a more equitable division of caregiving responsibilities, benefiting both families and society as a whole.